Bacterial diversity in a mine water treatment plant - Heinzel, Elke; Hedrich, Sabrina; Janneck, Eberhard; Glombitza, Franz; Seifert, Jana; Schlömann, Michael (Applied and environmental microbiology, 2009)
We investigated the microbial community in a pilot plant for treatment of acid mine water by biological ferrous iron oxidation using clone library analysis and calculated statistical parameters for further characterization. The microbial community in the plant was conspicuously dominated by a group of Betaproteobacteria affiliated with "Ferribacter polymyxa".